Mīnākṣī-sundareśvara : "Tiruviḷaiyāṭar̲ Purāṇam" in letters, design and art - Rajarajan, R. K. K. (Sharada Publishing House, 2013)
On Tiruviḷaiyāṭal (Sanskrit līlā) myths; from ancient to 18th century A.D.